Case Report: Successful Outcome for Refractory Diabetic Peripheral Neuropathy in Patients With Ultrasound-Guided Injection Treatment - Hu, Hua Qiong; Huang, Hailun; Huang, Jing; Leng, Ji Cui; Li, Mi; Tang, Chao; Li, Yan; Wu, Shan (Frontiers in Endocrinology, 2021)
Diabetic peripheral neuropathy is the most prevalent chronic complication of diabetes and is based on sensory and autonomic nerve symptoms. Generally, intensive glucose control and nerve nourishment are the main treatments. However, it is difficult to improve the symptoms for some patients; such cases are defined as refractory diabetic peripheral neuropathy (RDPN). In this paper, we present five patients treated with saline and mecobalamin by ultrasound-guided injection. The Visual Analog Scale and Toronto Clinical Scoring System were used to evaluate the symptoms, and the neuro-ultrasound scoring system and electrophysiological severity scale were evaluated by ultrasound and electrophysiological examination. In brief, ultrasound-guided hydrodissection may be a safe way to treat RDPN.